Mat lab/simulink based fault analysis of pv grid with intelligent fuzzy logic control mppt - Priyadarshi, Neeraj; Kr. Sharma, Amarjeet; Kr. Bhoi, Akash; N. Ahmad, S; Azam, Farooque; Priyam, S (International Journal of Engineering and Technology, 2018)
This paper mainly presents the fault analysis of Photovoltaic (PV) grid power system. The fuzzy logic controller (FLC) based intelligent maximum power point tracking (MPPT) algorithm has been employed in this work. Moreover, the hysteresis controller has been implemented for inverter control. Simulation results based on MATLAB/SIMULINK justify the effectiveness of the proposed PV power system under different fault operating conditions.Â